Enhancement of dissolution profile of poorly aqueous soluble atorvastatin calcium by binary and ternary solid dispersion techniques - Sarkar, MR; Hossin, A; Al Hossain, ASMM; Sikdar, KMYK; Raihan, SZ; Hossain, MH (Bangladesh Journal of Scientific and Industrial Research, 2021)
Atorvastatin calcium (ATV) is an HMG-CoA (3-hydroxy-3-methylglutaryl coenzyme A) reductase inhibitor commonly known as a cholesterol-lowering agent. As a poorly water-soluble drug its absolute bioavailability is very low. To increase the water solubility as well as oral bioavailability, different hydrophilic carriers were used in different ratios (1:0.5, 1:1 and 1:2) to prepare reproducible binary and ternary solid dispersion formulations of ATV by simple physical mixing (PM) and fusion or melting technique. In vitro dissolution studies results revealed that in all cases, the cumulative percent drug release from ATV ternary SD formulations were greater than binary formulations, some marketed products and pure ATV powder. The order of the carriers in enhancing the drug release was found as kollidon 90F > pregelatinized starch > lutrol> kollidon 12F (99.1%, 98.8%, 96% and 95% respectively) for ternary SD formulations whereas pure ATV powder and marketed products showed cumulative percentage release 70.8%, 68.9% (B1) and 73.1% (B2), respectively. The best-out performed ternary SD formulation ATV:Kollidon 90 F (1:2) were further characterized using FT-IR and SEM. SEM analyses indicated conversion of crystal drug to amorphous form and FT-IR data suggested that little or no interaction between the drug and polymer. Bangladesh J. Sci. Ind. Res.56(3), 165-176, 2021